2013
DOI: 10.3389/fnhum.2013.00643
|View full text |Cite
|
Sign up to set email alerts
|

Ten year neurocognitive trajectories in first-episode psychosis

Abstract: Objective: Neurocognitive impairment is commonly reported at onset of psychotic disorders. However, the long-term neurocognitive course remains largely uninvestigated in first episode psychosis (FEP) and the relationship to clinically significant subgroups even more so. We report 10 year longitudinal neurocognitive development in a sample of FEP patients, and explore whether the trajectories of cognitive course are related to presence of relapse to psychosis, especially within the first year, with a focus on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 66 publications
3
40
0
3
Order By: Relevance
“…A majority of the studies reported a relatively high degree of stability in cognitive functioning, with the exception of the study by Oie et al . (), and to some degree Barder and associates (), where a certain decline was found for verbal learning and memory.…”
Section: The Research Fundament Of the Neurodevelopmental Hypothesismentioning
confidence: 89%
“…A majority of the studies reported a relatively high degree of stability in cognitive functioning, with the exception of the study by Oie et al . (), and to some degree Barder and associates (), where a certain decline was found for verbal learning and memory.…”
Section: The Research Fundament Of the Neurodevelopmental Hypothesismentioning
confidence: 89%
“…This would suggest that although slight improvement may occur, individuals experiencing a psychotic illness fail to make normal gains in cognitive development (neurodevelopmental arrest), or even show evidence of deterioration (neuroprogression). Indeed, the available evidence indicates that a number of cognitive domains, such as language, processing speed and working memory, are impaired at psychosis onset, and remain stably impaired over the course of the illness [12,29,30 ]. However, there is evidence that other areas of cognition may be preserved at psychosis onset, with deterioration occurring as the illness progresses [12].…”
Section: Evidence For Cognitive Decline In Early Psychosismentioning
confidence: 93%
“…Among patients with chronic schizophrenia (CSz), cognitive impairment is diffuse and pervasive, with deficits typically 1 to 2 standard deviations below non-psychiatric control samples across various cognitive domains (Gold, 2004; Green, 2006; Heinrichs and Zakzanis, 1998). Cognitive impairment appears to be a relatively stable feature of schizophrenia (Barder et al, 2013b; Hoff et al, 2005), even across acute vs. remitted states (Nuechterlein et al, 1992), with limited response to antipsychotic treatment (Keefe et al, 2007; Rund, 1998). Cognitive impairment is present in first-episode schizophrenia (FESz; (Addington and Addington, 2002; Barder et al, 2013a; Gold et al, 1999; Hoff et al, 1999; Mohamed et al, 1999), and likely precedes the onset of illness in an attenuated form (Cornblatt et al, 1999; Hawkins et al, 2004; Lencz et al, 2006; Lewandowski et al, 2011; Seidman et al, 2010; Simon et al, 2007).…”
Section: Introductionmentioning
confidence: 99%